Job performance in the Malaysian Public Service: the roles of job demands-resources and subjective Wellbeing - Mohamad Hajari, Fatimah Hanum (2020)
For many years the Malaysian Public Service (MPS) has placed a huge emphasis on the job performance of its civil servants. Various initiatives and programs such as the Excellent Work Culture, National Integrity Plan and Clean, Efficient and Trustworthy Campaign have been put in place by the government to improve the performance of its civil servants and public image of its healthcare provision. Nevertheless, poor job performance manifested in delays in receiving treatment, negligence during treatment, poor diagnosis and errors in the delivery of medication remain widespread and as such, the MPS has been subject to much public criticism in recent times. Because the severity of the problem has not been systematically investigated, the current situation warrants a more detailed and evidence-based investigation into job performance in the MPS and the factors related to it. The present research was conducted in order to investigate the issue of poor job performance in Malaysian public hospitals by identifying the factors that enhance or hinder job performance and testing these inter-relationships using an evidenced-based framework of job demands, job/personal resources, subjective well-being and performance. A mixed methods approach with a sequential exploratory design was employed. In Study 1, interview sessions were carried out with participants at selected hospitals. The data collected from the interviews were used to create additional items for a larger-scale survey used in the Study 2. Study 1 found that job performance in the MPS was at a ‘moderate and acceptable level’ according to participants of the study. Majority participants were very enthusiastic about their work and workplace and believed that the reporting of incidents of poor job performance by the Malaysian Public Complaints Bureau and newspapers were grossly exaggerated largely based on isolated incidents. Nevertheless, participants did acknowledge that some employees did not perform as well as they could because of problems such as work overload and negative attitudes. Study 1 revealed that six factors affected job performance in the MPS: 1) work overload, 2) civil servants’ attitudes, 3) leadership and monitoring, 4) religious and spiritual beliefs, 5) training, knowledge and experience and 6) personal issues. Based on the moderated mediation analyses conducted in Study 2, it was found that job resources predicted work engagement and a particularly positively impacted when job demands were at moderate and high levels. Work engagement in turn, positively impacted job performance. The analyses also revealed a significant relationship between personal resources and job performance through job demands and organisational commitment. The moderated mediation between personal resources, organisational commitment and job performance can be seen at all level of job demands. The findings largely appear to be consistent throughout the study in that job resources are significantly related to work engagement and personal resources with organisational commitment, which in turn affects job performance. The implications of these findings are discussed in terms of existing literature and suggestions for further research are also included.